2007
DOI: 10.1177/153303460700600508
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hilar Stereotactic Body Radiation Therapy in the Rat

Abstract: Stereotactic Body Radiation therapy (SBRT) is an emerging modality of treatment for early stage non-small cell lung carcinoma. Concerns have arisen related to increased toxicities for medial tumors. We have developed a model of high dose, hypofractionated radiotherapy to the pulmonary hilum using the Leksell Gamma-Knife. Sprague-Dawley rats received hypofractionated SBRT to the unilateral lung hilum using a custom immobilization device on the Gamma Knife. Each animal was individually scanned, treatment planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, Timmerman et al reported that the risk of severe toxicity associated with SBRT was elevenfold higher in patients with centrally located lung tumors in comparison to that of patients whose tumors were peripheral [26]. After this landmark report cautioned us against using SBRT to tumors within 2 cm from the main bronchus, a few reports have been published recently which are affirmative for SBRT to the pulmonary hilum [1,12,27]. Joyner et al treated nine patients who had centrally located lung tumors by SBRT with a dose of 36 Gy in three or six fractions (BED 10 ; 57.6 Gy or 46.8 Gy).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Timmerman et al reported that the risk of severe toxicity associated with SBRT was elevenfold higher in patients with centrally located lung tumors in comparison to that of patients whose tumors were peripheral [26]. After this landmark report cautioned us against using SBRT to tumors within 2 cm from the main bronchus, a few reports have been published recently which are affirmative for SBRT to the pulmonary hilum [1,12,27]. Joyner et al treated nine patients who had centrally located lung tumors by SBRT with a dose of 36 Gy in three or six fractions (BED 10 ; 57.6 Gy or 46.8 Gy).…”
Section: Discussionmentioning
confidence: 96%
“…Tinnel et al analyzed the correlation between the risk of interstitial pneumonia and the irradiated lung volume in rodent experiments [27]. They mentioned that the bronchus could tolerate therapy when a small volume was irradiated with a very high dose, such as a single fraction of 80-160 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent exposure of the contralateral eye, corresponding collimator conduits are plugged. The device has also been used for irradiation of the unilateral mainstem bronchus in rats as a model for radiation-induced bronchial damage [79]. A stereotactic positioning device for mice [74] is intended for irradiating the rear flank [80] and mammary gland [81] to investigate colorectal and breast cancer models, respectively.…”
Section: Gamma Knife ®mentioning
confidence: 99%
“…In their experiment, the mainstream bronchus was irradiated with 4 mm or 8 mm collimators. It was found that the bronchus well tolerated small volume (4 mm) of very high dose of radiotherapy but a bigger volume (8 mm) encompassing the surrounding support stroma and normal tissue produced cellular atypia, interstitial pneumonitis, bronchial and vascular damages (Tinnel et al, 2007). Finally, Belzile et al showed that administration of octreotide, a drug used in acromegaly and other types of digestive pathologies, prior to GKRS acted as a radioprotective agent on rat parotid glands one month after irradiation (Belzile et al, 2009).…”
Section: Focused Radiation Targeted Outside the Brainmentioning
confidence: 99%
“…This visual targeting was deemed adequate because the target was the external eye of the animal, but could not be used for internal organ targeting. This device and method are reported elsewhere (Dynlacht et al, 2006;Dynlacht et al, 2008) and the coordinates were finally confirmed by CT scan (Tinnel et al, 2007). Im et al (Im et al, 2006) also created a stereotactic device for rat consisting of a plate with ear plugs, incisor bar and a sliding Y and Z scales.…”
mentioning
confidence: 92%